2017
DOI: 10.1242/dev.146969
|View full text |Cite
|
Sign up to set email alerts
|

Vegfd modulates both angiogenesis and lymphangiogenesis during zebrafish embryonic development

Abstract: Vascular endothelial growth factors (VEGFs) control angiogenesis and lymphangiogenesis during development and in pathological conditions. In the zebrafish trunk, Vegfa controls the formation of intersegmental arteries by primary angiogenesis and Vegfc is essential for secondary angiogenesis, giving rise to veins and lymphatics. Vegfd has been largely thought of as dispensable for vascular development in vertebrates. Here, we generated a zebrafish vegfd mutant by genome editing. vegfd mutants display significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 69 publications
(114 reference statements)
4
67
0
1
Order By: Relevance
“…The N-terminal cleavage that then results in full activity of VEGFC is regulated by collagen-and calcium-binding EGF domains 1 (CCBE1) protein and executed by a disintegrin and metalloprotease with thrombospondin motifs-3 (ADAMTS3) protease (Jeltsch et al, 2014;Le Guen et al, 2014;Roukens et al, 2015). Specific proteases that activate VEGFD by cleavage of the N-terminal propeptide are so far unknown, suggesting that VEGFD has evolved to function in distinct angiogenic and lymphangiogenic responses (Bower et al, 2017;Bui et al, 2016;McColl et al, 2003).…”
Section: Alternative Splicing and Processing Of Vegf Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal cleavage that then results in full activity of VEGFC is regulated by collagen-and calcium-binding EGF domains 1 (CCBE1) protein and executed by a disintegrin and metalloprotease with thrombospondin motifs-3 (ADAMTS3) protease (Jeltsch et al, 2014;Le Guen et al, 2014;Roukens et al, 2015). Specific proteases that activate VEGFD by cleavage of the N-terminal propeptide are so far unknown, suggesting that VEGFD has evolved to function in distinct angiogenic and lymphangiogenic responses (Bower et al, 2017;Bui et al, 2016;McColl et al, 2003).…”
Section: Alternative Splicing and Processing Of Vegf Family Membersmentioning
confidence: 99%
“…VEGFA, in addition to inducing angiogenesis, can also stimulate lymphatic vessel expansion (Nagy et al, 2002;Wirzenius et al, 2007). Despite its similarity to VEGFC, VEGFD is dispensable for developmental lymphangiogenesis in mammals (Baldwin et al, 2005), although its absence leads to somewhat decreased lymphatic vessel caliber in the skin (Paquet-Fifield et al, 2013) and inhibition of facial lymphangiogenesis in zebrafish (Bower et al, 2017).…”
Section: Vegfr Signaling In Lymphatic Vesselsmentioning
confidence: 99%
“…In the craniofacial region of the embryo, LECs emerge from the common cardinal vein and fuse with LECs that emerge from the primary head sinus to form a complex facial lymphatic network; meanwhile, a population of mural LECs also forms around the brain (Astin et al, 2014;Bower et al, 2017a;Okuda et al, 2012;van Lessen et al, 2017;Venero Galanternik et al, 2017). Both vegfc and vegfd zebrafish mutants show reductions in, and double vegfc, vegfd mutants show major or complete loss of, craniofacial lymphatic development (Bower et al, 2017a(Bower et al, , 2017b. Zebrafish mutants lacking Flt4 (the homolog of human VEGFR3) show a complete block in trunk lymphangiogenesis and specification of trunk LECs (with no induction of the LEC transcription factor Prox1), but they do not display a complete loss of craniofacial lymphangiogenesis (Shin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish mutants lacking Flt4 (the homolog of human VEGFR3) show a complete block in trunk lymphangiogenesis and specification of trunk LECs (with no induction of the LEC transcription factor Prox1), but they do not display a complete loss of craniofacial lymphangiogenesis (Shin et al, 2016). We have previously shown that zebrafish Vegfd can bind Kdr but not Kdrl (Bower et al, 2017b); however, it was assumed that the contribution to facial lymphangiogenesis by zebrafish Vegfd occurs via activation of the lymphangiogenic zebrafish receptor Flt4.…”
Section: Introductionmentioning
confidence: 99%
“…Le rôle du VEGF-D est moins bien compris. Chez le poisson zèbre, il régule l'angiogenèse et la lymphangiogenèse au cours du développement [20]. Chez la souris, des expériences de double invalidation des gènes Vegfd et Sox18 suggèrent qu'ils contrôlent le développement vasculaire en modulant l'activité de SOX18 [21].…”
Section: Revuesunclassified